Using moringa leaf extract to reduce the effect of abiotic stress on crop productivity - Agada, Odu Odo; Hassan, Siti Aishah; Othman, Radziah; Megat Wahab, Puteri Edaroyati (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
The paper reviews the effectiveness of Moringa leaf allelopathy in alleviating the impact of abiotic stress on crop productivity when applied exogenously. It was observed that whereas synthetic growth enhancing substances can be used effectively to limit the effect of stress on crops, there cost remained prohibitive. The paper showed that moringa leaf extract (MLE) is a functional alternative as the raw material and technology as its production was low cost, accessible and simple. Also discussed is the mechanism of stress alleviation by MLE and the best approach for using it effectively. It was highlighted that foliar spray, applied at the latter growth stages (after seedling establishment) was the most effective approach.